Pragmatic Proficiency in Hospitality Emails: Hotel Management Students' Language Politeness and Message Effectiveness - Makmun Syaifudin; Dita Anggi Purbasari (Journal of English Language and Education, 2026)
Effective email communication is essential in a hospitality business as it exhibits service professionalism and influences guest satisfaction. However, research into hospitality students' pragmatic competency in producing guest service emails remains limited, especially in the context of EFL vocational education in Indonesia. By comparing two groups in terms of formality, politeness, mitigation techniques, message effectiveness, grammatical accuracy, and the use of native-like polite language, this study seeks to assess the pragmatic quality of guest service emails written by hospitality management students. This study used a quantitative descriptive-comparative design enhanced with qualitative content analysis. It comprised 43 hospitality management students from an Indonesian vocational higher education institution. Data were collected using a guest service email writing assignment and analyzed using pragmatic and linguistic assessment criteria. The study found that Class A exhibited significantly higher levels of formality and politeness by frequently employing professional registers, mitigating devices, and service-oriented language. Instead, both groups revealed almost identical patterns of grammatical errors, most of which were non-fatal and had no substantial impact on communication. The study further discovered that polite emails were not always more effective if they lacked a straightforward response or sufficient follow-up information. These findings underline the significance of pragmatic competence in hospitality communication and recommend that English for Hospitality teaching should emphasize a professional register, politeness strategies, and authentic service-oriented email practices.